Mitochondrial Dynamics Drive Muscle Stem Cell Progression from Quiescence to Myogenic Differentiation - Olivia Sommers; Rholls A. Tomsine; Mireille Khacho (Cells)
From quiescence to activation and myogenic differentiation, muscle stem cells (MuSCs) experience drastic alterations in their signaling activity and metabolism. Through balanced cycles of fission and fusion, mitochondria alter their morphology and metabolism, allowing them to affect their decisive role in modulating MuSC activity and fate decisions. This tightly regulated process contributes to MuSC regulation by mediating changes in redox signaling pathways, cell cycle progression, and cell fate decisions. In this review, we discuss the role of mitochondrial dynamics as an integral modulator of MuSC activity, fate, and maintenance. Understanding the influence of mitochondrial dynamics in MuSCs in health and disease will further the development of therapeutics that support MuSC integrity and thus may aid in restoring the regenerative capacity of skeletal muscle.